Enhancing Students’ Conceptual Understanding and Learning Independence in Chemical Equilibrium using E-Module Based Guided Discovery Learning - Sa'adah, Siti Imroatus; Ikhsan, Jaslin (Jurnal Tadris Kimiya, 2023)
Chemical equilibrium is considered abstract so it requires visualization by analogy through electronic modules combined with interactive multimedia teaching materials. This study aims to examine the influence of a guided discovery learning-based e-module on chemical equilibrium on the development of conceptual understanding and self-directed learning among 11th grade science students enrolled in the control and experimental groups. The research framework employed in this study follows a research and development (R&D) model. The participants were selected using the cluster random sampling technique. The e-module, developed based on GDL principles, was administered to 72 science 11th grade students through a quasi-experimental design involving a posttest-only control group. The research employed conceptual understanding test of chemical equilibrium and a self-directed learning questionnaire as data collection instruments. The disparities in conceptual understanding and self-directed learning between the control and experimental groups were assessed using the MANOVA (Hotteling's trace) test. There is a significant difference in both the overall and individual abilities of conceptual understanding and learning independence between students who used electronic modules based on GDL and those who did not, as indicated by simultaneous significance levels of 0.001 and individual significance levels of 0.009 and 0.004, all of which are smaller than 0.05.